Penerapan Jaringan Sensor Nirkabel dan Internet of Things (IoT) pada Pertanian Terpadu - Suhardi; Dedi Triyanto; Irma Nirmala (STMIK Budi Darma, 2024)
Integrated farming system is an approach to managing plants, livestock, and fish along with their environment to create optimal results. The development of integrated agriculture is advancing with technologies such as Wireless Sensor Networks and the Internet of Things (IoT), enabling remote monitoring and control of agricultural environmental conditions. For this purpose, an application called